PENERAPAN PROBLEM-BASED LEARNING DENGAN SIKLUS LESSON STUDY UNTUK MENINGKATKAN KEMAMPUAN MENULIS ESAI ARGUMENTATIF - Anak Agung Putri Maharani (SPHOTA: Jurnal Linguistik dan Sastra, 2019)
ABSTRACT The skill to write argumentative essas as a necessity in the 21st century is crucial for students to hone their critical thinking skills. Having been designed as a classroom action research, the researcher applied Problem-Based Learning with Lesson Study cycle that answered the following two research questions: (a) Can students' argumentative essay writing skill be improved by applying Problem-Based Learning with Lesson Study cycle? And (b) How was the student's response to their implementation? The research subjects consisted of 36 students of IVA semester in English Education Study Program, Faculty of TeacherTraining and Education, Mahasaraswati Denpasar University. To collect data, test and questionnair were administered as research instruments. Data were analyzed descriptively quantitative and qualitative (interactive model). It was found that the application of Problem-Based Learning and Lesson Study was able to improve students' argumentative essay writing skill and the students gave positive response towards their application for the improvement of learning. Key words: argumentative essay, Lesson Study, Problem-Based Learning.